2014
DOI: 10.1371/journal.pone.0088004
|View full text |Cite
|
Sign up to set email alerts
|

RNase A Does Not Translocate the Alpha-Hemolysin Pore

Abstract: The application of nanopore sensing utilizing the α-hemolysin pore to probe proteins at single-molecule resolution has expanded rapidly. In some studies protein translocation through the α-hemolysin has been reported. However, there is no direct evidence, as yet, that proteins can translocate the α-hemolysin pore. The biggest challenge to obtaining direct evidence is the lack of a highly sensitive assay to detect very low numbers of protein molecules. Furthermore, if an activity based assay is applied then the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Furthermore, since in our experiments RNase A was suspended in a slightly basic buffer (pH ¼ 8), the selection of a negative f p value is supported by previous reports. 26 Note that when EP is excluded (f p ¼ 0), the EK velocity is still higher (by $3 times) in comparison to the EK velocity response with f p ¼ À10 mV (Figure 6(c)). A lower EK velocity is expected to reduce the drag force on the protein molecules, contributing to improve the dielectrophoretic trapping.…”
Section: Parametric Sweep Studymentioning
confidence: 88%
See 3 more Smart Citations
“…Furthermore, since in our experiments RNase A was suspended in a slightly basic buffer (pH ¼ 8), the selection of a negative f p value is supported by previous reports. 26 Note that when EP is excluded (f p ¼ 0), the EK velocity is still higher (by $3 times) in comparison to the EK velocity response with f p ¼ À10 mV (Figure 6(c)). A lower EK velocity is expected to reduce the drag force on the protein molecules, contributing to improve the dielectrophoretic trapping.…”
Section: Parametric Sweep Studymentioning
confidence: 88%
“…It has been reported that RNase A f p can vary from À0.010 to 0.010 V approximately under different conditions of ionic strength and pH. 26 So far, there is lack of literature reporting conductivity of proteins, especially for RNase A, although there are some reported values available for other proteins that vary in a very wide range. 22,[28][29][30] As we experimentally observed streaming or trapping DEP for both proteins (native and PEGylated) in positive mode, we set r p ¼ 1000 lS/cm, one order of magnitude higher than r m , to guarantee positive DEP theoretical predictions.…”
Section: Parametric Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, owing to the lack of a PCR-like technique for amplifying proteins, it is very difficult to even acquire direct evidences to prove protein translocation. 12 Recently, Akeson and his coworkers demonstrated that a recombinant ubiquitin-like protein Smt3 bearing a polyanionic peptide at its C-terminus was unfolded and pulled through a α-hemolysin (α-HL) nanopore by the AAA+ unfoldase ClpX. 13 Almost at the same time, Bayley's team reported that a thioredoxin protein tethered to a negatively charged oligonucleotide could also be unfolded and translocated through the α-HL nanopore by an applied voltage.…”
mentioning
confidence: 99%